IMPACT OF WORK STRESS AND WORK MOTIVATION TOWARD TEACHER PERFORMANCE IN VOCATIONAL SCHOOL 1 KALIANDA SOUTH LAMPUNG - Uzair Albazi; Hazairin Habe; Trisnowati Josiah (Saburai International Journal of Social Sciences and Development, 2020)
This study aims to analyze Work Stress and Work Motivation for Teacher Performance. The population in this study were all 88 SMK Negeri 1 Kalianda South Lampung School Teachers. The problem in this study is the high level of work stress and the low motivation of teachers so that it has an impact on the performance of teachers in SMK Negeri 1 Kalianda, South Lampung. The sampling technique uses saturated samples. The results showed that work stress and work motivation did not affect the performance of teachers in SMK Negeri 1 Kalianda, South Lampung. The results of data analysis on work stress variables show that the sig value of 0.026 (smaller than 0.05) which means, job stress affects performance. On the variable work motivation on performance, the results of the study also showed that work motivation did not affect the performance of a teacher based on the results of the t test that had been done. For work motivation itself shows that the sig value of 0.443 (greater than 0.05) which means, work motivation has no effect on performance. While Work Stress and Work Motivation jointly affect the performance of teachers in Kalianda 1 South Lampung Vocational School proven by sig values of 0.049 kurang dari 0.05. With a contribution value of 0.611 Adjusted R Square value is positive, the independent variable (work motivation and work stress) is able to explain the variance of the dependent variable by 61.1%, and the rest is explained by other variables that are not in this study